PAROXYSMAL SUPRAVENTRICULAR TACHYCARDIA: DIAGNOSIS, EMERGENCY CARE - G.T. Mamedova (Web of Journals Publishing, 2024)
Paroxysmal tachycardia is an attack of sharply rapid heartbeat with a heart rate from 130 to 200 or more per minute. Usually, the attack begins suddenly and also ends suddenly. The duration of the attack is from several seconds to several hours and days. With paroxysmal tachycardia, a focus of excitation appears in any part of the conduction system of the heart, generating electrical impulses of high frequency. Such a focus can occur in the cells of the conduction system of the atria or ventricles.
Keywords: atrial flutter, paroxysm of supraventricular tachycardia, paroxysm of ventricular tachycardia, paroxysm of atrial fibrillation, paroxysm of atrial flutter, glaucoma, high myopia.